Price-level targeting when there is price-level drift - Christina Gerberding; Rafael Gerke; Felix Hammermann (Deutsche Bundesbank, 2010)
Recent research has shown that optimal monetary policy may display considerable price-level drift. Proponents of price-level targeting have argued that the costs of eliminating the price-level drift may be reduced if the central bank responds flexibly by returning the price level only gradually to the target path (Gaspar et al., 2010). We revisit this argument in two variants of the New Keynesian model. We show that in a two-sector version of the model which allows for changes in relative prices across sectors, the costs of stabilisation under price-level targeting remain much higher than under inflation targeting for all policy-relevant horizons. Our conclusion is that extending the policy horizon is not a panacea to reduce the costs of eliminating pricelevel drift.
Keywords: E58; E42; E31; 330; price-level targeting; optimal monetary policy; commitment; Inflation Targeting; Preisspanne; Geldpolitik; Soziale Kosten; Ungleichgewichtstheorie; Mehr-Sektoren-Modell; Theorie